2013
DOI: 10.1111/jen.12096
|View full text |Cite
|
Sign up to set email alerts
|

Culturing chelifers (Pseudoscorpions) that consume Varroa mites

Abstract: Chelifers (Pseudoscorpions) are generalist predators of small prey such as mites. Their occasional presence in honeybee hives suggests potential to exploit them as part of a management programme against Varroa mites (Varroa destructor), a significant pest of honeybees. Two species of native New Zealand chelifers Nesochernes gracilis and Heterochernes novaezealandiae, shown to consume Varroa mites, were collected from commercial nucleus hives or in litter surrounding the hives. Methods for mass‐rearing the chel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…In Europe, Chelifer cancroides was interested in predatory species of beekeeping (Schiffer, 2017) and showed the most promising roles for the biological control of Varroa (Read et al, 2014). Rangel and Ward (2018) reported that predatory mite (Stratiolaelaps scimitus; Mesostigmata: Laelapidae) could control Varroa under laboratory and field conditions.…”
Section: Biological Agentsmentioning
confidence: 99%
“…In Europe, Chelifer cancroides was interested in predatory species of beekeeping (Schiffer, 2017) and showed the most promising roles for the biological control of Varroa (Read et al, 2014). Rangel and Ward (2018) reported that predatory mite (Stratiolaelaps scimitus; Mesostigmata: Laelapidae) could control Varroa under laboratory and field conditions.…”
Section: Biological Agentsmentioning
confidence: 99%
“…Fagan et al (2012) reported that 25 pseudoscorpions were sufficient to manage the population of Varroa within hives. Mass-rearing methods for two pseudoscorpions (Nesochernes gracilis and Heterochernes novaezealandiae) were developed in New Zealand, and N. gracilis showed the most promising role for biological control of Varroa (Read et al 2014). Also, a molecular technique based on detection of Varroa DNA in extractions of pseudoscorpion DNA was developed to confirm the predation in commercial hives without the need for observation (van Toor et al 2015).…”
Section: Predatorsmentioning
confidence: 99%
“…Chelifer cancroides (chelifer) was collected from lucerne nesting material of leaf-cutting bees (Megachile rotundata) in a chicken coop at Prebbleton, Canterbury, New Zealand, in December 2013. The pseudoscorpions were maintained on a diet of fruit flies (Drosophila melanogaster) and apterous aphids (Acyrthosiphon pisum), in gauze-vented plastic containers containing fine sand for nesting material and bark for refuge as per Read, Howlett, Donovan, Nelson, and van Toor (2014). Approximately, 30 adults were in each container.…”
Section: Pseudoscorpion Culturesmentioning
confidence: 99%